Evaluation of the Valencia’s Public Library using “discussion groups” and “survey” enchained method - Cortés Villalba, Carmina; Gil-Leyva, Isidoro (Revista General de Información y Documentación, 2012)
We evaluated the services of the Valencia Public Library (VPB) through opinion from users. For it two discussion groups were created involving ten people in total. The results of the discussion groups were used to make a pilot survey and later a final survey was completed for four hundred VPB users. We conclude that VPB meets generally to the expectations of citizens, although there are areas for improvement such as schedules, better information and services activities and signage, among other aspects. It also confirms the chained system survey-focus groups as an enhanced system that optimizes the design of the survey.